MHC-1B carried exosomes derived from tubular epithelial cell induced by the EGFR mimotope inhibit macrophage activation in renal fibrosis - Guo, Jin; Liu, Xuanqi; Song, Haoming; Gu, Yong; Niu, Jianying; Yang, Lin (Extracellular Vesicle (Online), 2023)
The high prevalence of chronic kidney disease (CKD) is a significant public health burden worldwide. Renal fibrosis is an inevitable pathological process in almost all CKD cases. To date, the available treatments to prevent or delay renal fibrosis progression are limited. Epidermal growth factor receptor (EGFR) mimotope has been demonstrated to alleviate renal fibrosis in the unilateral ureteric obstruction (UUO) model as a type of vaccine. Further observations suggested that the EGFR mimotope can inhibit the activation of macrophages, which play a vital role in renal fibrosis. In the current study, we explored the link triggered by the EGFR mimotopes between tubular epithelial cells (TECs) and macrophages. A series of experiments indicated that EGFR mimotope immunization can inhibit the activation of THP-1 macrophages by TEC-derived exosomes. Injection of these exosomes ameliorated renal fibrosis in the UUO model. Mechanism analysis suggested that the major histocompatibility complex-1B (MHC-1B) was the key molecule in the TECs exosomes induced by EGFR mimotope immunization and is regulated by ribosomal protein L6 (RPL-6). This study revealed a new specific working path of the EGFR mimotope and suggests that the application of the EGFR mimotope can be extended to other immune-related disorders.